The Use of Cell-penetrating Peptide for Delivery of Recombinant Transcription Factor DNA into Primary Human Fibroblast - Melinda Remelia; Budiman Bela; Silvia Tri Widyaningtyas; Radiana Dhewayani Antarianto; Nuzli Fahdia Mazfufah; Jeanne Adiwinata Pawitan (Cell and BioPharmaceutical Institute, 2023)
Background: Reprogrammed cell therapy has not been applied for clinical purposes due to the malignancy issue. The aim of this study was to design the recombinant vector of the transcription factors and analyze the effectiveness of cell-penetrating peptide delivering system for human primary fibroblast transfection to avoid the malignancy issue.Materials and methods: The constructions of CCAT/enhancer binding protein alpha (CEBPA), hepatocyte nuclear factor 4 alpha (HNF4A), nuclear receptor subfamily 1 group I member 2 (NR1I2) were confirmed with DNA digestion and sequencing. Breast reduction (BRED) and palate (PAL) tissue were used as human primary fibroblast sources. The transcription factors were delivered into BRED and PAL with recombination of avian leukosis sarcoma virus (ALSV), human immunodeficiency virus (HIV) matrix, and regulator of expression of virion proteins (Rev) (ALMR), tagged with enhanced green fluorescence protein (eGFP). Post-transfection cells were then cultivated with optimized medium. Gene expression was measured with quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR).Results: Gene expression levels of CEBPA, HNF4A, NR1I2, glutamate-ammonia ligase (GLUL), albumin (ALB), and cytochrome P450 (CYP) were increased. Transfection with ALMR, which were more efficient in BRED than PAL fibroblasts may have the advantage in autologous cell therapy for elderly patients.Conclusion: Transfection of transcription factors to human primary fibroblast may be performed by using constructions of plasmid as designed in this study.Keywords: recombinant plasmid, hepatocyte-like cells, primary fibroblasts, recombinant peptide, cell reprogramming, autologous cells therapy